Assessing Coastal Vulnerability to Extreme Waves and Abrasion in Bandar Lampung City: Implications for Spatial Pattern and Infrastructure Adaptation - Asbi, Adnin Musadri; Rahman, Yudha; Rasyid, Fachri Muhammad; Siregar, Diyanti Isnani (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2026)
Coastal cities in Southeast Asia face dual challenges of rapid urbanization and increasing climate pressures, demanding robust integration of risk assessment into spatial planning. This study assesses the vulnerability of Bandar Lampung City's coastal area to extreme waves and abrasion, analyzing implications for its spatial plan. Using a standard hazard index and a spatial overlay against the city's Regional Spatial Plan (RTRW), the research identifies a 'Medium' hazard classification across all four studied sub-districts. Crucially, this classification is not driven by significant hydrodynamic forces but is substantially amplified by anthropogenic vulnerabilities. A development-centric spatial policy has led to the dominance of residential and industrial land use on susceptible coastal typologies, coupled with a critical lack of protective vegetation. The analysis exposes a significant misalignment between planning and risk reduction, revealing a state of 'planned vulnerability' where over 400 hectares designated for future industrial and residential development lie directly within the hazard zone. This physical exposure is compounded by high social vulnerability in densely populated communities and the placement of critical public infrastructure in at-risk areas. Situated within the city's multi-hazard context including flooding, tsunamis, and accelerating climate change impacts, these findings highlight a systemic conflict between short-term development objectives and long-term resilience. The study concludes that effective adaptation requires a fundamental shift beyond project-based solutions towards the systemic integration of multi-hazard risk assessment into urban governance and spatial planning.